Analysis of cervical spine loading in rugby scrummaging: a computer simulation approach - Cazzola, D.; Trewartha, G.; Preatoni, E. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Musculoskeletal modelling is widely used in biomechanics for the analysis and simulation of human motion. A modelling approach allows estimates of the internal load on specific anatomical structures, and the individual muscle forces that govern movement execution. Within the analysis of impact events in rugby union, modelling can help the understanding of the mechanisms of acute and chronic cervical spine injuries, starting from experimental measures of external load on the player, and progressing to the estimation of stresses acting on the internal cervical structures. During this part of the applied session, we will use a novel musculoskeletal model and previously collected experimental data (forces and kinematics) to analyse the cervical spine loading experienced during a rugby scrum. An open-source biomechanical software (OpenSim 3.2) will be used to set up and run inverse and forward dynamics pipelines to calculate joint moments and joint reaction forces, and to analyse "what if…" scenarios.